The Effect of Financial Literacy and Attitude on Financial Management Behavior and Satisfaction - Yap, Richard Josua Christian; Komalasari, Farida; Hadiansah, Ihsan (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Finance aspect is one of the most important things in a family in order to develop their life every day. However, the heads of family, husband and wife should be able to manage the stability and development of family’s financial with a purpose to acquire financial satisfaction. Inspired by the developed previous research, this research examined the effect of financial literacy and financial attitudes on financial management behavior and financial satisfaction of married individuals in Kelurahan Sepanjang Jaya, Bekasi. Financial literacy, financial attitudes were examined as independent variable. Financial management behavior became the mediator variable; as independent but also dependent variable. Financial satisfaction will examined as dependent variable. The sample was 200 respondents married individuals, chosen by using non-probability sampling. Two-step Multiple Regression Analysis is used to test the hypotheses. The result shows financial attitude was the most influencing variable toward financial management behavior; also financial management behavior was the most influencing variable toward financial satisfaction. Researcher recommends that giving more attention to financial attitude and financial management behavior is important to achieve financial satisfaction. Therefore, this research result contributes to increase married individuals’ awareness that financial satisfaction can be achieved by having good financial attitude and management behavior.